What Should Blog Search Look Like? - Hearst, Marti A.; Hurst, Matthew; Dumais, Susan (SSM 2008, 2008)
Blog search has not yet reached its full potential. In this position paper, we suggest that more could be done to accommodate the task of ﬁnding good blogs to read, especially with respect to matching a desired taste or style of writing. We propose a faceted navigation interface as a good starting point for blog and author search, and that search oriented around people and their writings will lend itself well to advanced interfaces. We also argue that blog search is probably best integrated with search on other forms of timely social media for the task of determining what is currently being thought about a particular topic.